Genomic basis of deep‐water adaptation in Arctic Charr (Salvelinus alpinus) morphs. Issue 18 (12th August 2021) - Kess, Tony; Dempson, J. Brian; Lehnert, Sarah J.; Layton, Kara K. S.; Einfeldt, Anthony; Bentzen, Paul; Salisbury, Sarah J.; Messmer, Amber M.; Duffy, Steven; Ruzzante, Daniel E.; Nugent, Cameron M.; Ferguson, Moira M.; et al.
Abstract: The post‐glacial colonization of Gander Lake in Newfoundland, Canada, by Arctic Charr ( Salvelinus alpinus) provides the opportunity to study the genomic basis of adaptation to extreme deep‐water environments. Colonization of deep‐water (>50 m) habitats often requires extensive adaptation to cope with novel environmental challenges from high hydrostatic pressure, low temperature, and low light, but the genomic mechanisms underlying evolution in these environments are rarely known. Here, we compare genomic divergence between a deep‐water morph adapted to depths of up to 288 m and a larger, piscivorous pelagic morph occupying shallower depths. Using both a SNP array and resequencing of whole nuclear and mitochondrial genomes, we find clear genetic divergence ( F ST = 0.11–0.15) between deep and shallow water morphs, despite an absence of morph divergence across the mitochondrial genome. Outlier analyses identified many diverged genomic regions containing genes enriched for processes such as gene expression and DNA repair, cardiac function, and membrane transport. Detection of putative copy number variants (CNVs) uncovered 385 genes with CNVs distinct to piscivorous morphs, and 275 genes with CNVs distinct to deep‐water morphs, enriched for processes associated with synapse assembly. Demographic analyses identified evidence for recent and local morph divergence, and ongoing reductions in diversity consistent with postglacial colonization. Together, these results show that Arctic Charr morph divergence has occurred through genome‐wide differentiation and elevated divergence of genes underlying multiple cellular and physiological processes, providing insight into the genomic basis of adaptation in a deep‐water habitat following postglacial recolonization.